2022
DOI: 10.1111/all.15247
|View full text |Cite
|
Sign up to set email alerts
|

Interdependencies of cellular and humoral immune responses in heterologous and homologous SARS‐CoV‐2 vaccination

Abstract: Background Homologous and heterologous SARS‐CoV‐2 vaccinations yield different spike protein‐directed humoral and cellular immune responses. This study aimed to explore their currently unknown interdependencies. Methods COV‐ADAPT is a prospective, observational cohort study of 417 healthcare workers who received vaccination with homologous ChAdOx1 nCoV‐19, homologous BNT162b2 or with heterologous ChAdOx1 nCoV‐19/BNT162b2. We assessed humoral (anti‐spike‐RBD‐IgG, neutral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 64 publications
5
20
0
Order By: Relevance
“…Although neutralizing antibody titers were lower in subjects who had received 2 doses of mRNA vaccine than in patients, these antibodies displayed higher avidity. This observation is in line with previous reports of a significant increase in neutralization and avidity after the administration of a second vaccine dose [ 17 , 33 ]. However, this immune response was not retained in the case of the Omicron variant, for which both neutralizing titers and avidity were lower.…”
Section: Discussionsupporting
confidence: 93%
“…Although neutralizing antibody titers were lower in subjects who had received 2 doses of mRNA vaccine than in patients, these antibodies displayed higher avidity. This observation is in line with previous reports of a significant increase in neutralization and avidity after the administration of a second vaccine dose [ 17 , 33 ]. However, this immune response was not retained in the case of the Omicron variant, for which both neutralizing titers and avidity were lower.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the COV-ADAPT study has presented the results obtained in HCW receiving various vaccination protocols. Homologous ChAdOx1 nCoV-19, homologous BNT162b2 or heterologous ChAdOx1nCoV-19/BNT162b2 vaccinations protocols have induced different Spike protein-directed humoral and cellular immune responses 46 . An Israeli study has shown that BNT162b2, homologous booster dose was associated with a lower rate infection rate 47 .…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In the COV-ADAPT cohort, we recently studied the humoral and cellular immune responses and their interdependencies following different vaccine combinations before (T1) and up to 3 months after the second immunization (T2). 12 This follow-up investigated the stability of long-term immune responses and aimed to identify predictive markers. Thus, we assessed humoral (anti-spike-RBD-IgG, neutralization capacity and avidity) and cellular (spike-induced T-cell interferonγ release) immune re- The last group was not analyzed separately due to the low n-number (for characterization of study participants see Table S1).…”
Section: Long-term Effects Of Homologous and Heterologous Sars-cov-2 ...mentioning
confidence: 99%
“… 10 , 11 In the COV‐ADAPT cohort, we recently studied the humoral and cellular immune responses and their interdependencies following different vaccine combinations before (T1) and up to 3 months after the second immunization (T2). 12 This follow‐up investigated the stability of long‐term immune responses and aimed to identify predictive markers. Thus, we assessed humoral (anti‐spike‐RBD‐IgG, neutralization capacity and avidity) and cellular (spike‐induced T‐cell interferon‐γ release) immune responses 3–7 months after the second immunization (T3) in blood samples of 320 healthcare workers of the COV‐ADAPT cohort with previous homologous ChAdOx1 nCoV‐19 (ChAdOx1, n = 26), homologous BNT162b2 ( n = 49), heterologous ChAdOx1/BNT162b2 ( n = 243) or heterologous ChAdOx1 /mRNA‐1273 ( n = 2) vaccinations (Figure S1 ; all participants provided written informed consent).…”
Section: Figurementioning
confidence: 99%